Assessing the public understanding of democracy through conjoint analysis - Seki, Katsunori (Frontiers in Political Science, 2023)
Global support for democracy is puzzling in the time of alleged backlash toward democracy. Building on recent studies on democratic support that take into consideration heterogeneity in the subjective perceptions of democracy, I conducted a conjoint analysis and examined the trade-offs among various democratic values that the citizens might face when they think of democracy. Using an original dataset of 2,206 respondents, sampled from Japanese adult population, I found that the procedural view of democracy played the most important role when Japanese people evaluated a country's democracy level. In their view, a lack of free and fair elections and disenfranchisement of certain groups were more detrimental to democracy than a shortage of checks and balances, economic growth, and social welfare. In addition, the analysis shows that factors representing the minoritarian view and the substantive view of democracy play an undeniable role in citizens' democracy evaluations, which confirms the discrepancies between how students of democratization conceptualize and how ordinary people think of democracy today.